Analisis Strategi Blue Ocean PT Darya-Varia Laboratoria TBK. - Amanda Diasha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This case study analyzes the implementation of the Blue Ocean Strategy by PT Darya-Varia Laboratoria Tbk, a leading pharmaceutical company in Indonesia, to create added value and avoid intense market competition. Using strategic management theory and the Blue Ocean Strategy model, the research identifies opportunities for innovation, operational efficiency improvement, and market expansion. The findings indicate that implementing this strategy enables the company to develop competitive advantages through product innovation, quality enhancement, and integrated digital technology. By focusing on unmet market needs and customer loyalty programs, PT Darya-Varia Laboratoria successfully expands its market share without facing direct competition while simultaneously enhancing its reputation and overall performance.